Group health coaching for the underserved: a case report. Issue 1 (2nd January 2020) - Schultz, Cynthia S.; Stuckey, Claire M.; Lawson, Karen
ABSTRACT: This case report features an integrative group health coaching (IGHC) experience that incorporates mind-body-skills exercises, goal setting and facilitated discussions to help group participants move forward in their sense of personal well-being. Four participants from a diverse, underserved population, completed the four weekly sessions at a student-led free health clinic. The facilitators applied their skills and knowledge in health and wellness coaching, and in psychology to lead this group. The pre- and post-group drawings assessment demonstrated that participants generally improved important aspects of their personal well-being. The participants broadened their perspectives, experienced self-efficacy, and generally improved their sense of well-being. This report outlines the process of conducting an IGHC programme for practitioners and may serve as a feasibility study for future research.